“Glomus tympanicum”: Three cases – Three approaches - Filipe, Joana (2011)
Glomus jugulo-tympanicum, also referred to as paraganglioma jugulo-tympanicum, is considered the most common primary benign tumor of the middle ear.Clinical survaillance, radiation therapy and surgical resection, with or without previous embolization, are considered valid therapeutical options, therefore, every case should be individualized.The authors present a literature review of this pathology, reporting three glomus jugulo-tympanicum cases with different clinical evolutions and distinct therapeutic managements, highlighting the factors that influenced the treatment decision.